USE OF WORDPRESS SYSTEMS FOR MONITORING KNOWLEDGE OF STUDENTS IN DISTANCE LEARNING: LearnPress окуу курстарынын долбоорун колдонуу (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The research work on the subjects included the creation of an information model of the educational environment with the regulation of distance learning and training of students and distance learning. Research with the help of information technology with the aim of identifying the means of distance learning and educational programs in the form of distance learning. Methods were used to create an application program for distance learning of the state programming language. The development of theoretical and applied aspects is shown through the creation of a distance education management complex using Internet technologies and appropriate software. One of them developed a distance learning program. Results have been obtained that lead to new research in the field of determining the level of education of students, as well as the conditions for the formation of distance learning. The developed software package allows you to check the level of knowledge of students in distance learning and establish a connection between the university and the student. Therefore, we recommend using WordPress to test students' knowledge and identify new research directions in the field of distance learning.
Keywords: distance learning system; Internet; WordPress; learning process; information technology